Procuring Fast Delivery: Sole Sourcing with Information Asymmetry - Cachon, Gérard P.; Zhang, Fuqiang (Management Science, 2006)
This paper studies a queuing model in which a buyer sources a good or service from a single supplier chosen from a pool of suppliers. The buyer seeks to minimize the sum of her procurement and operating costs, the latter of which depends on the supplier’s lead time. The selected supplier can regulate his lead time, but faster lead times are costly. Although the buyer selects the supplier to source from (possibly via an auction) and dictates the contractual terms, the buyer’s bargaining power is limited by asymmetric information: The buyer only has an estimate of the suppliers’ costs, while the suppliers know their costs precisely. We identify a procurement mechanism that minimizes the buyer’s total cost (procurement plus operating). This mechanism is not simple: It is a numerically derived nonlinear menu of contracts. Therefore, we study several simpler mechanisms: e.g., one that charges a late fee and one that specifies a fixed lead-time requirement (no menus, no nonlinear functions). We find that simple mechanisms are nearly optimal (generally within 1% of optimal) because asymmetric information conveys significant protection to the supplier, i.e., the supplier is able to retain most of the benefit of having a lower cost. Renegotiation is another concern with the optimal mechanism: Because it does not minimize the supply chain’s cost, the firms can be both better off if they throw away the contract and start over. Interestingly, we find that the potential gain from renegotiation is relatively small with either the optimal or our simple mechanisms. We conclude that our simple mechanisms are quite attractive along all relevant dimensions: buyer’s performance, supply chain performance, simplicity, and robustness to renegotiation.